Eletroforese capilar (CE-C4D) aplicada à análise rápida de amônio, difenidramina, arginina, ácido ascórbico e aspartato em formulações farmacêuticas - Costa, Brenda Maria de Castro (2018)
In the present work, capillary electrophoresis with contactless capacitive coupled conductivity detection (CE-C4D) was used for the development of two rapid methods for simultaneous determination of: (i) diphenhydramine (DIP) and ammonium; (ii) arginine (ARG), ascorbic acid (ASC) and aspartate (ASP). The proposed methods are characterized by analyzes with run times less than 50 s and can be used in quality control of raw materials and pharmaceutical formulations having such compounds in its composition. In the simultaneous determination of the compounds of the group (i), the BGE was composed by 30 mmol L-1 of 2 (N-morpholino) ethanesulfonic acid (MES) and 15 mmol L-1 LiOH (pH=6,0). The limits of detection (LOD) were 0.04 and 0.02 mmol L-1 for NH4+ and DIP, respectively. The method was accurate with recovery values between 97 and 106%. The results obtained with the proposed method were statistically similar (confidence level of 95%) to those obtained by HPLC (DIP) and Kjeldahl method (NH4+). For the simultaneous determination of the compounds of the group (ii), the BGE was composed by 20 mmol L-1 N- [Tris(hydroxymethyl)methyl]-3 aminopropanesulfonic acid (TAPS) and 10 mmol L-1 of NaOH (pH=8,7). The LOD were 0.01, 0.035 and 0.02 mmol L-1 for ARG, ASC and ASP, respectively. In addition, the proposed method presented satisfactory results in the recovery test (100% to 105%) for samples containing ARG, ASC and ASP. Calibration curves for all species showed correlation coefficients greater than 0.996 and RSD values in the stability study less than 2.9% (n = 10). Furthermore, the CE-C4D methods are simple, generates a minimum amount of waste (lower environmental impact), are low cost (equipment and maintenance) and has a high analytical frequency: ~90 injections h-1 (i) and ~78 injections h-1 (ii).